Journal Economics, business & accountancy : WOOLWORTHS AUSTRALIA AND WALMART US: BEST PRACTICES IN SUPPLY CHAIN COLLABORATION - Arli, Verdi , Dylke, Sean:Burgess, Rosie:Campus, Romain:Soldo, Evita (PPPM Perbanas, 2013)
This study analyses retail industries with the efforts of their supply chain collaboration (SCC) frommanufacturers to consumers. It also describes the ways of identifying collaboration partners and buildingpartnership for sharing information, thus representing the best practices in such efforts. The successof building the collaboration in terms of supply chain is described through the observation and analyseson the journey undertaken by both Walmart US, and Woolworths Australia.